Are the residents of former Yugoslavia still exposed to elevated PCB levels due to the Balkan wars? Part 2: Passive air sampling network - Klánová, Jana; Kohoutek, Jirí; Cupr, Pavel; Holoubek, Ivan (Environment international, 2007)
Many Eastern European countries suffer the lack of data on concentrations of persistent organic pollutants in the environmental matrices. This absence of information is preventing the local authorities from taking the adequate actions to protect the people and environment. This is even more alarming in the countries recently affected by the wars where the chemicals released to the environment during the military operations can cause a significant ecological damage and health effects on the population. A potential of passive air sampling technique as a tool capable of providing seasonally and spatially resolved information about the local sources and levels of contamination was explored in this study as a first step to the establishment of a cost-effective long-term monitoring in this area. The passive air samplers proved to be a powerful technique capable of detecting the concentrations ranging over four orders of magnitude providing the information very comparable with the conventional techniques.
Keywords: polychlorované bifenyly; Bosna a Hercegovina; vzduch; vedení války; hodnocení rizik; Air; Polychlorinated Biphenyls; látky znečišťující vzduch; Air Pollutants; Bosnia and Herzegovina; Croatia; Chorvatsko; Risk Assessment; Warfare